Thank You to Our 2021 Reviewers. Issue 4 (18th April 2022) - AghaKouchak, Amir; Caylor, Kelly; Dalin, Carole; de Beurs, Kirsten; Diffenbaugh, Noah; Guan, Dabo; Kopp, Robert; Kroll, Jesse; Mishra, Vimal; Reed, Patrick M.; Zhang, Xin; Kruse, Sarah; et al.
Abstract: We are delighted to publish the names of the 613 peer reviewers who submitted 904 reviews in 2021. We express our deep appreciation for your thoughtful comments and suggestions on manuscripts submitted to Earth's Future . Key Points: Earth's Future thanks its reviewers who contributed in 2021 In 2021, 613 reviewers submitted 904 reviews The average time to the first decision in 2021 was around 80 days